Treacher Collins Syndrome: A Case Report and Review of Literature - Effat Khodadadi; Zahra Dehghan (Mazandaran University of Medical Sciences, 2019)
Introduction: Treacher Collins Syndrome (TCS) is an inherited and rare, autosomal dominant condition of craniofacial malformation with varying degrees of penetrance and expression that has been described extensively in the scientific literature with more than 250 cases reported. We presented a 7-year-old boy with TCS. The etiology, clinical features, differential diagnosis and treatment planning have been discussed. In addition, we also reviewed 10 varied cases of TCS. Case Presentation: Syndromic appearance of abnormal orbits, eyes, ear, and facial bones, along with normal physical and dental development and intelligence quotient were observed in a 7-year old boy referred to the Pediatric Department of Babol Dental School. The patient had no family history of any syndrome, and after reviewing his complete medical records and diagnosing oral and dental problems, the treatment plan was devised. Due to the high risk of caries in the patient, he was followed up every three months. Conclusions: Early detection, treatment and particular attention to every case of TCS can reduce disease symptoms. Psychological consultation can improve the quality of life for these patients.